Liquidity Biases and the Pricing of Cross-sectional Idiosyncratic Volatility - Han, Yufeng; Lesmond, David (Review of Financial Studies, 2011)
We model a microstructure effect on daily security returns, embodied by zero returns and the bid-ask spread, and derive a closed-form solution for the resulting bias in the estimated idiosyncratic volatility. Our empirical tests show that controlling for the bias eliminates the ability of idiosyncratic volatility estimates to predict future returns. We also find a significant reduction in the pricing ability of idiosyncratic volatility after exogenous shocks to liquidity evidenced in the 1997 reduction in the quotes to sixteenths and the 2001 decimalization. Finally, minimizing liquidity's influence on the estimated idiosyncratic volatility, by orthogonalizing the percentage of zero-return and spread effects on the estimated idiosyncratic volatility, demonstrates that the resulting idiosyncratic volatility estimate has little pricing ability.